The end of consociational power-sharing? Its causes and what can Be done - John Nagle (Cogent Social Sciences)
Consociational power-sharing has been described as ‘hegemonic’ as the international community’s preferred institutional framework for ending intrastate conflicts. Consociationalism’s dominance is illustrated in the emergence of a wave of new post-war power-sharing agreements two decades after the end of the Cold War. Consociational advocates have recommended power-sharing solutions for various contemporary conflicts, including Yemen, Ukraine, and Syria. Yet, despite claims of consociationalism’s hegemony, there have not been any new consociations to end intrastate conflict despite a proliferation of civil wars globally. This article seeks to address the question of why relatively few new successful consociations have been implemented in 15 years. By turning to the issue of adoptability in consociationalism – the favourable factors for implementing consociationalism – the article examines two key issues: (1) unsupportive international context; (2) complex conflicts. While the article does not foreclose the possibility of new consociational pacts to end intrastate conflicts, it calls on fresh thinking about refining power-sharing to make it more amenable to the contemporary international context.